Ocular Biometric Changes Following Scleral Buckle Surgery for Rhegmatogenous Retinal Detachment - SHILPA Y D,; SOWMYA SHREE B V,; HEMALATHA B C,; KALPANA BADAMI NAGARAJA,; KAVITHA L TUMBADI, (Nepalese Journal of Ophthalmology, 2026)
Introduction: Rhegmatogenous retinal detachment (RRD) is separation of neurosensory retina and Retinal Pigment Epithelium, due to full-thickness retinal breaks. Scleral Buckling (SB) is extraocular procedure done to reattach retina by counteracting vitreoretinal traction and altering globe’s geometry. Objective: To study various ocular changes and visual outcomes after buckling among patients of RRD.Methodology: A longitudinal observational study was conducted with prospective data collection in a tertiary health care centre from 2019 November to 2021 December after ethical clearance. It included 40 RRD patients who underwent scleral buckling (sizes 279, 276, and 281), recruited by consecutive sampling technique. Study excluded tractional detachment or pathologies affecting retinal visualisation. All patients were evaluated for visual acuity, refraction, intraocular pressure (IOP), axial length (AL) and anterior chamber depth (ACD) both preoperatively and post-operatively at one week, one month, and three months. Statistical analysis was done with Microsoft Excel Sheet using appropriate statistical tests.Result: Visual acuity showed significant (p-value